Affect alongside context: Imagining the psychosocial - Young, Lisa Saville (PINS-Psychology in Society, 2016)
BOOK REVIEW Frosh, Stephen (ed) (2015) Psychosocial imaginaries: Perspectives on temporality, subjectivities and activism. Studies in the Psychosocial series. Hampshire, UK & New York: Palgrave MacMillan.